I. Turgieniew jako protomodernista. Sztuka „Miesiąc na wsi” w kontekście cyklu esejów К. Greenberga „Obrona modernizmu”. Zapowiedź nowego stylu artystycznego - Waligórska-Olejniczak, Beata (Studia Rossica Posnaniensia, 2011)
Clement Greenberg is considered as one of the greatest and most influential American critics of the late 20th century. Understanding modern and postmodern discussions in the world of literature and fine arts seems to be impossible without the profound knowledge of Greenberg's opinions. The aim of the studies in this article is the comparative analysis of I. Turgenev's drama A Month in the Country and fundamental principles of Greenberg's theory of modernism, the attempt to generate the inner relationships between those two works of art. Treating the aforementioned drama as the model piece of Turgenev's dramaturgy we focus on the parametres which build up the openness of the play, emphasise the innovative character of the text in the context of the changes of the Great Theatre Reform. The interpretation of Turgenev's play in the view of global artistic tendencies shows the uniqueness of his work of art. The comparative method of the analysis helps to discover the encoded features which will influence modernist way of thinking, eliminating the differences between the word and other ways of artistic expression.